Key management infrastructure design and novel techniques to establish secure communications in critical infrastructures. (2017) - Pramod, T.C.; Sunitha, N.R.
The industrial automation and control systems (IACS) play a vital role in critical infrastructures to optimise the processes and control the activities remotely. As the proliferation of deliberate security attacks on these systems is increasing, ensuring reliable operations of these systems with safety and security is prominent. The key management infrastructure (KMI) ensures the proper management of secret keys and cryptographic keying materials which are used to secure the system. From IACS perspective, this paper addresses the security issues, challenges and parameters that need to be considered for designing an effective KMI for IACS. Also, by considering the constraints and required key management features, an efficient KMI is proposed for supervisory control and data acquisition (SCADA) systems using the polynomial key establishment scheme. The objective of the proposed KMI for SCADA systems is to support broadcasting, multicasting, join and leave, key update and pairwise communications between the SCADA devices. Comparison of the proposed scheme with existing schemes is reported.